The Role of Home Reading in Foreign Language Teaching and Its Organization At The English Lessons (Eurasian Journal of Learning and Academic Teaching, 2021)
The issue that we consider in this paper - the role of home reading in foreign language teaching and the organization of foreign language lessons - is one of the most important up-to-date problems. I would like to make a reservation at once, the concept home reading - a reading of the work in a foreign language in the original. It seems to us only the language of art works by matching usually standards of modern literary language is not replaceable as a model for the study of a foreign language, and the role that the sample is especially great, as is taught as secondary linguistic community.